P69-T Orthostatic tolerance and the significance of heart rate variability analysis in children with multiple sclerosis. Issue 7 (July 2019) - Gergont, Aleksandra; Kroczka, Sławomir; Gajda, Beata; Kaciński, Marek
Abstract : Background: Multiple sclerosis (MS) can lead to orthostatic intolerance and cardiovascular autonomic dysfunction. Previous studies have determined sympathovagal imbalance using analysis of heart rate variability (HRV) in adults with MS. Aim: The aim of the study was comparison of HRV between recently diagnosed pediatric patients with multiple sclerosis and healthy controls during the rest as well as during passive tilting. Methods: The examination was performed in 18 children with MS aged 15–17 years, hospitalized at the Chair of Pediatric and Adolescent Neurology and in 18 children admitted to the hospital due to Bell's palsy, constituting an age-matched control group. HRV was evaluated during the rest and during a 10-min 70 degrees head-up passive tilting using Task Force Monitor 3030i/3040i. Results: Postural orthostatic tachycardia syndrome was the most common manifestation of orthostatic intolerance in 5 children with False positive syncope occurred in one boy from control group. Heart rate (HR) did not differ between groups during the rest but was higher during titling in patients with There were differences in results of HRV ratio between groups not only during the rest but also during tilting. Conclusion: These findings revealed that our pediatric population with multiple sclerosis had decreased orthostatic tolerance with common postural orthostatic tachycardia syndrome. Previous studies have determined that sympathetic dysfunction was related to the progression of disability in multiple sclerosis. Our results suggested a relative hypo activity of the sympathetic nervous system also in recently diagnosed pediatric patients.